Empire and Democracy. A critical reading of Michael Ignatieff - E. Korstanje, Maximiliano (Nómadas. Critical Journal of Social and Juridical Sciences, 2013)
Empires expand their hegemony combined two contrasting forces; one is violence the second is characterized by persuasion. Ideology works in these contexts, as an efficient instrument of self-indoctrination whereby dominated cultures accept the cultural matrix of empire. In this vein, the present essay-review not only questions the employment of human rights in the liberal thought, but also tries to respond to the conceptual problems of liberalism to understand terrorism. Based on two seminal texts written by the liberal Michael Ignatieff, we formulate the thesis that liberalism supports the war against terror because of its doctrine of self-determination.